Design, Construction, and Control for an Underwater Vehicle Type Sepiida. Issue 5 (8th May 2021) - Garcia, M.; Castillo, P.; Campos, E.; Lozano, R.
SUMMARY: A novel underwater vehicle configuration with an operating principle as the Sepiida animal is presented and developed in this paper. The mathematical equations describing the movements of the vehicle are obtained using the Newton–Euler approach. An analysis of the dynamic model is done for control purposes. A prototype and its embedded system are developed for validating analytically and experimentally the proposed mathematical representation. A real-time characterization of one mass is done to relate the pitch angle with the radio of displacement of the mass. In addition, first validation of the closed-loop system is done using a linear controller.